Peran Kepala Desa Dalam Meningkatkan Kualitas Pelayanan Publik Menuju Desa Yang Akuntabel (Studi di desa peresak kecamatan Narmada Kabupaten Lombok barat - Yolanda Alfira Febriana; Hera Sukma Rahmaniah; Baiq Yani Rosanti; Ida Sugiastutik; Elsa Mayora (Journal of Social and Education, 2025)
This research aims to find out what the role of the village head is in improving Quality of Public Services Towards an Accountable Village, especially in Presak village, Narmada, West Lombok Regency.  The method used in this research is qualitative descriptive, data collection is carried out by directly conducting interviews and observations. The results of this research indicate that public services in Pesak village are in good condition can be said to be quite good based on the results of our observations and interviews do we find data - data that shows that role the village head insists on improving the quality of public services towards accountable village is good.  In this case, there are 3 roles that can improve public services: (1) the role of the village head (2) village officials, and (3) village secretary